Employer and employer association matters in Australia in 2019. (June 2020) - Sheldon, Peter; Thornthwaite, Louise
The May federal election appeared particularly important to employers' views of their industrial relations' interests. Employers and their associations had long steeled themselves against an unwelcome Labor victory, fearing Labor's promises of substantial changes to industrial relations' structures, processes and outcomes as well as taxation. Associations appeared busier than ever, representing employers through politics-related public relations, lobbying and media. With enterprise bargaining withering and most wages stagnant, Labor's defeat encouraged associations and the re-elected government to engage in another, for-now stalled, attack on what remains of unions' capacity to collectively protect employees. They have also focused on emergent (individual) employment law challenges for employers but have mainly deflected on widespread evidence of wage underpayment. While the political context again strongly favours employers and their associations, they face substantial challenges from rising media and public criticisms over employers' widespread abuses of their social licence to operate.